The History of the Anglo-Saxons - Turner, Sharon (Cambridge University, 2017)
Sharon Turner (1768-1847) practised as a solicitor in London, but as a young man he had become involved in the study of Anglo-Saxon and Icelandic literature and history. Published 1799-1805, this four-volume work was a benchmark in Anglo-Saxon studies, drawing on manuscripts in the British Museum.